Interventions to significantly improve service uptake and retention of HIV‐positive pregnant women and HIV‐exposed infants along the prevention of mother‐to‐child transmission continuum of care: systematic review. Issue 2 (8th December 2017) - Vrazo, Alexandra C.; Firth, Jacqueline; Amzel, Anouk; Sedillo, Rebecca; Ryan, Julia; Phelps, B. Ryan
Abstract: Objectives: Despite the success of Prevention of Mother‐to‐Child Transmission of HIV (PMTCT) programmes, low uptake of services and poor retention pose a formidable challenge to achieving the elimination of vertical HIV transmission in low‐ and middle‐income countries. This systematic review summarises interventions that demonstrate statistically significant improvements in service uptake and retention of HIV‐positive pregnant and breastfeeding women and their infants along the PMTCT cascade. Methods: Databases were systematically searched for peer‐reviewed studies. Outcomes of interest included uptake of services, such as antiretroviral therapy (ART) such as initiation, early infant diagnostic testing, and retention of HIV‐positive pregnant and breastfeeding women and their infants. Interventions that led to statistically significant outcomes were included and mapped to the PMTCT cascade. An eight‐item assessment tool assessed study rigour. PROSPERO ID: CRD42017063816. Results: Of 686 citations reviewed, 11 articles met inclusion criteria. Ten studies detailed maternal outcomes and seven studies detailed infant outcomes in PMTCT programmes. Interventions to increase access to antenatal care (ANC) and ART services ( n = 4) and those using lay cadres ( n = 3) were most common. Other interventions included quality improvement ( n = 2), mHealth ( n = 1), and counselling ( n = 1). One study described interventions in an Option B+ programme. Limitations included lack of HIV testing and counselling and viral load monitoring outcomes, small sample size, geographical location, and non‐randomized assignment and selection of participants. Conclusions: Interventions including ANC/ART integration, family‐centred approaches, and the use of lay healthcare providers are demonstrably effective in increasing service uptake and retention of HIV‐positive mothers and their infants in PMTCT programmes. Future studies should include control groups and assess whether interventions developed in the context of earlier 'Options' are effective in improving outcomes in Option B+ programmes.